Untreated Pain a 'Scandal of Global Proportions' (Bangladesh Journal of Medical Science, 2014)
DOI: http://dx.doi.org/10.3329/bjms.v13i3.17694 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.249-250